Overrepresentation of Adopted Adolescents at a Hospital-Based Gender Dysphoria Clinic - Shumer, Daniel E. (Transgend Health, 2017)
Purpose: We have noted a greater than expected prevalence of adopted children presenting to our multidisciplinary gender program for evaluation of gender dysphoria. Methods: A retrospective review of 184 patient charts was conducted to assess the prevalence of adopted children presenting to gender clinic. Results: Fifteen of 184 patients seen were living with adoptive families (8.2%). This is significantly higher than expected based on U.S. census data. Conclusion: Adopted children are referred to our gender program more than would be expected based on the percentage of adopted children in our state and the United States at large. This may be due to a true increased risk of gender dysphoria in adopted children, or could represent presentation bias. Gender programs should be prepared to provide assessments for adopted children. Further work is needed to understand the relationship between adopted status and gender development.